Pengaruh Larangan Mudik Dan Pembatasan Sosial Berskala Besar (PSBB) Terhadap Penjualan Kerupuk Sanjai Di Kota Payakumbuh - Vicy Andriany; Tezi Asmadia; Hafifah Kamariah Putri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The main problem in this thesis is the decline in sales due to the Large-Scale Social Restrictions (PSBB) policy and a prohibitions going home that occurred in the city of Payakumbuh. The purpose of this discussion is to know the effect of Large-Scale Social Restrictions (PSBB) and a prohibition on the sale of sanjay crackers in the city of Payakumbuh. The type of research that the author uses is field research with a quantitative approach. The data collection technique that the author uses is using interviews and questionnaires. Data management is done by using a statistical application, namely the IBM SPSS V16 application. From the research that the authors did, it can be concluded that Large-Scale Social Restrictions (PSBB) and homecoming bans affected sales of sanjay crackers in Payakumbuh City. Influence level Large-Scale Social Restrictions (PSBB) and a ban on going- home sales of sanjay crackers in the city of Payakumbuh amounted to 57.7%.